Microbial evaluation of implant surface - Fabio Furquim; Tatiana Miranda Deliberador; Maria Cecilia Lopes Giacomel; Suyany Weiss; João César Zielak; Rafaela Scariot (Universidade Estadual de Campinas, 2021)
Aim: The aim of the present study was to evaluate the microbial contamination in internal and external walls of cone morse implant walls. Methods: Eleven patients with edentulous mandibular posterior area were selected to received dental implants, divided into groups: submerged (S), non-submerged (NS), and immediately loaded (IL). Microbiological evaluations (microorganisms' number, aerobic and anaerobic colony forming units (CFU) number and microorganisms' qualification) were divided into internal and external collection of the implant walls, at different stages: T0 (surgical procedure), T2 (suture removal), T4 (reopening S group), T6 (suture removal S group), and T8 (abutment placement in S and NS). All data were submitted to statistical analyses, with confidence level of 0.05. Results: There was difference in number of microorganisms observed over time within the same group (p < 0.05). A difference was observed in CFU when evaluated within the same group over time (p < 0.05), except for the IL group. In internal collection, a predominance of non-formation of microorganisms was observed at T0 in all groups, while formation of Gram-positive Diplococci and Gram-positive Bacilli was observed at T8 (p>0.05). In external collection, an increase in number of microorganisms was observed at T0. Conclusion: There was no difference in microbial contamination among the evaluated groups. The microorganism's colonization changed over time.